2021
DOI: 10.1155/2021/3087071
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Peri-Implant Bone Loss in the Occlusal Load Transfer to the Supporting Bone in terms of Magnitude of Stress, Strain, and Stress Distribution: A Finite Element Analysis

Abstract: Background and Objective. Marginal bone loss around dental implants is one of the most prevalent complication, and its biomechanical impact may be critical for treatment prognosis. The objective of this study was to evaluate the influence of marginal bone loss around dental implants in the occlusal load transfer to the bone in terms of magnitude of stress and strain and distribution of such transferred stress. Methods. Three models of a single internal connection bone level-type implant inserted into a posteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…In this preliminary study, bone loss might be associated with an increase in stress in the implants and prosthetic components, especially when using an aftermarket screw. These findings are in agreement with those of previous FEA studies regarding aftermarket abutments [ 8 , 42 , 43 , 44 , 45 ]. When an unfit aftermarket screw encounters another factor of marginal bone loss, compared with the use of an OEM screw in the presence of bone loss, the stress accumulation and destructive force caused by the unfit screw are compounded.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this preliminary study, bone loss might be associated with an increase in stress in the implants and prosthetic components, especially when using an aftermarket screw. These findings are in agreement with those of previous FEA studies regarding aftermarket abutments [ 8 , 42 , 43 , 44 , 45 ]. When an unfit aftermarket screw encounters another factor of marginal bone loss, compared with the use of an OEM screw in the presence of bone loss, the stress accumulation and destructive force caused by the unfit screw are compounded.…”
Section: Discussionsupporting
confidence: 93%
“…In this experiment, an angular bone defect, which is more common in clinical practice, was used, and the results still showed that it had a considerable impact on the entire implant system. Perez-Pevida et al [ 43 ] found that different morphologies of bony defects affected the strain distribution and amount in an implant system.…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies have found that marginal bone loss induced by fretting wear is one of the most common implant complications, and biomechanical impact is critical for treament success. [ 45 ] Thus, tangential fretting at the main contacting interface in the cervical region of the implant should be avoided. [ 9 ] We evaluated the tangential fretting wear behavior of FCBIC and cortical bone and compared it with that of commonly used implant materials by simplifying it to a titanium ball‐on‐material flat configuration in vitro ( Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…Osteons can even be pulled out of their envelope through the tension, which is called the "osteonal pulled-out" effect [19,20]. As a result, the bone's elasticity vanishes in the vicinity of stiff endosseous implant designs (especially once the implants are functionally loaded and mineralization increases along the IC) [21].…”
Section: Physio-biological Explanation Of Clinical Observationsmentioning
confidence: 99%